Experimental tests of the thermal behaviour of new sustainable bio-packaging food boxes - Madhan, Sasi (2021)
This experimental task was performed using 8 sustainable Bio-Boxes in the thermal chamber in the laboratory. The air is forced from the refrigerator, and it is used to control the temperature inside the thermal chamber. The goal of the performed task is to evaluate the thermal behaviour of the bio Boxes made from different material, such as sugarcane bagasse and PLA material with respect to time. The test was performed to lower the temperature inside the chamber to its minimum air temperature inside the cold chamber. The results show that the SCB 4 has noticed changes in its mechanical properties (Tensile Strength) and it also shown some moisture absorbing when compared to other Bio boxes. Furthermore, this kind of Bio packaging materials needs more research to improve their mechanical and barrier properties and minimise the use of plastic containers for food packaging industry.